Sidohibah: Web-Based Application for Grant Applications for Private Elementary School Facilities and Infrastructure in Sidoarjo Regency - Kurnia Ningtiyas; Ade Eviyanti; Hamzah Setiawan; Azmuri Wahyu Azinar (CV. Media Digital Publikasi Indonesia, 2026)
The process of applying for facilities and infrastructure grants at private elementary schools in Sidoarjo Regency is still mostly handled manually, which sometimes results in delays, recording errors, and difficulties in collecting data for each application. Therefore, researchers developed a web-based information system called Sidohibah. The system was developed in stages, adapting to user needs. The implementation results show that this system is capable of improving administrative efficiency while strengthening transparency in grant management.